QUALITY ANALYSIS OF BIODIESEL FROM PALM OIL - Rahmawati Rahmawati (Marina Chimica Acta, 2016)
Biodiesel (fatty acid methyl esters or FAME) an alternative fuel to substitute diesel oil or diesel fuel made from oils or fats of vegetable or animal. Oils commonly used for biodiesel fuel, among others palm oil. Biodiesel is produced through the transesterification of oils or esterification of fatty acids. The research objective was to determine the quality of biodiesel from palm oil reflux results through the process of esterification and transesterification. Transesterification reaction is the formation of esters and glycerol from trigliserin (fat/oil) with methanol. Transesterification is a type of equilibrium reaction (reversible, where the addition of NaOH catalyst (chemical catalysts) can accelerate the achievement of a state of equilibrium. The results showed that rendamen biodiesel was obtained by 77% and quality parameters that defined American Society for Testing and Materials (ASTM D6751) has meet the standards in terms of density of 0.8654 g/mL, saponification 5.2979 mg KOH /g of oil, iodine number 18.9184 g I2/100g.Keywords: Quality, biodiesel, palm oil